Clinical Outcome Measures in Arthroscopic Meniscectomy: Clinician versus Patient Completed Knee Scores - Al-Dadah, Oday; Shepstone, Lee; Donell, Simon T. (Revista Brasileira de Ortopedia, 2022)
Objective The aim of the present study was to investigate the difference between clinician-completed and patient-completed outcome scores in detecting improvement following arthroscopic meniscectomy in patients with meniscal tears of the knee.Methods Thirty-four patients with meniscal tears were prospectively assessed using 9 clinical outcome measures. The five clinician-completed knee scores included the Tegner Activity Score, the Lysholm Knee Score, the Cincinnati Knee Score, the International Knee Documentation Committee (IKDC) Examination Knee Score, and the Tapper and Hoover Meniscal Grading Score. The four patient-completed knee scores included the IKDC Subjective Knee Score, the Knee Outcome Survey – Activities of Daily Living Scale (KOS-ADLS), the Short Form-12 Item Health Survey (SF-12), and the Knee Injury and Osteoarthritis Outcome Score (KOOS). Twenty-nine of the 34 patients underwent an arthroscopic meniscectomy and were reassessed with all 9 outcome scores upon their follow-up review.Results A significant longitudinal improvement was observed in 4 of the 5 clinician-completed scores (Tegner [p < 0.001], Lysholm [p = 0.004], Cincinnati [p = 0.002] and Tapper and Hoover [p < 0.001], but not in the IKDC Examination [p = 0.332]. However, the IKDC Subjective score (p = 0.021) was the only patient-completed score to demonstrate significant improvement postoperatively.Conclusion Overall, clinician-completed scoring systems were found to be inconsistent with those of patient-completed instruments. The mode of administering outcome measures can have a significant influence on the outcome results both for research and for clinical practice. A combination of both a clinician-completed with a patient-completed instrument may be a more balanced approach to assessing and quantifying meniscus tears and the outcome following arthroscopic meniscectomy.
Keywords: meniscus; meniscectomy; patient reported outcome measures; Lysholm knee score